2021
DOI: 10.1002/pmrj.12692
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of trends in Medicare utilization and reimbursement in Physical Medicine & Rehabilitation: 2012 to 2017

Abstract: Introduction There is an absence of literature describing Medicare utilization by physiatrists, despite their key role in treating Medicare enrollees with qualifying disabilities and common neuromusculoskeletal conditions. Objective To analyze Medicare data regarding physiatrists and their beneficiaries, services, and reimbursement, as well as trends in utilization and geographic distribution. Design and Setting Retrospective analysis of publicly available Centers for Medicare & Medicaid Services data for Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Operationally, optimizing electronic medical record functions and educating providers leads to more accurate condition coding and, subsequently, more appropriate compensation for quality care. 5 , 8 , 22 , 23 Consistent, accurate coding should reduce individual-level variation in HCC risk scores, particularly for lifetime and clinically manageable preventable conditions. While risk scores are likely to vary with treatable condition diagnoses, variation driven by those treatable conditions that are preventable or HCCs that indicate worsening or persistent severity point to opportunities for improved care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Operationally, optimizing electronic medical record functions and educating providers leads to more accurate condition coding and, subsequently, more appropriate compensation for quality care. 5 , 8 , 22 , 23 Consistent, accurate coding should reduce individual-level variation in HCC risk scores, particularly for lifetime and clinically manageable preventable conditions. While risk scores are likely to vary with treatable condition diagnoses, variation driven by those treatable conditions that are preventable or HCCs that indicate worsening or persistent severity point to opportunities for improved care.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Conversely, between 2012 and 2017, the average HCC risk score of beneficiaries with a psychiatric condition increased substantially. 22 Failure to accurately document the type and severity of conditions leads to coding irregularities, negatively impacting providers engaged in CMS value-based payment models. 6 , 9 , 23 , 24 Although the linkage between HCC risk score and providers’ reimbursement rates incentivizes coding accuracy, this evidence suggests that providers and regions suffer from coding variations.…”
Section: Introductionmentioning
confidence: 99%
“…A prior study also found increased reimbursement rates for botulinum toxin injections, and justified this finding in that the neurotoxin was a more cost-effective treatment for spasticity in physical medicine and rehabilitation. 21 Another study looking at common dermatology services also reported a few significant increases in reimbursement for noninvasive procedures (ultraviolet light treatments) despite an overall decreasing trend in Medicare reimbursement. 22 Overall, there may be a trend in Medicare reimbursement toward minimally invasive, cost-effective treatments.…”
Section: Discussionmentioning
confidence: 99%